ANALISIS STUDI KELAYAKAN BISNIS PT PESTA PORA ABADI (MIE GACOAN) DITINJAU DARI ASPEK PASAR, OPERASIONAL, KEUANGAN, DAN SYARIAH - Dini Vientiany; Agfahmi Dinata; Citra Annisa Ginting; Sadepa Putri Br Sinulingga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to evaluate the business feasibility of PT Pesta Pora Abadi (Mie Gacoan) through a comprehensive business feasibility study approach. Using qualitative descriptive methods, this study analyzes various business dimensions to ensure business sustainability in the competitive culinary industry. The results of the marketing strategy analysis indicate that Mie Gacoan has successfully dominated the youth market through its economical price positioning and the use of viral content on social media. From an operational analysis perspective, the company's readiness is evident in its strategic location selection, outlet capacity of up to 140 seats, and the implementation of 24-hour operating hours to maximize productivity. The legitimacy of the business is strengthened by the fulfillment of legal aspects and halal certification from the Indonesian Ulema Council (MUI), which guarantees safe consumption for the wider community. Financially, this business model is considered very feasible because it is able to maintain stable profitability through high sales volume. This study concludes that Mie Gacoan has a strong business model and is worthy of continued national expansion.